2011
DOI: 10.1186/1472-6882-11-129
|View full text |Cite
|
Sign up to set email alerts
|

Boswellia sacra essential oil induces tumor cell-specific apoptosis and suppresses tumor aggressiveness in cultured human breast cancer cells

Abstract: BackgroundGum resins obtained from trees of the Burseraceae family (Boswellia sp.) are important ingredients in incense and perfumes. Extracts prepared from Boswellia sp. gum resins have been shown to possess anti-inflammatory and anti-neoplastic effects. Essential oil prepared by distillation of the gum resin traditionally used for aromatic therapy has also been shown to have tumor cell-specific anti-proliferative and pro-apoptotic activities. The objective of this study was to optimize conditions for prepari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
130
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(144 citation statements)
references
References 64 publications
(71 reference statements)
12
130
1
1
Order By: Relevance
“…Accumulating evidence of the antitumor activity of essential oils (18,19) supports this material as one of these drug sources. In a previous paper (1), we showed that the EO of M. officinalis was cytotoxic to several cancer cell lines but its effect on GBM cells was not investigated.…”
Section: Discussionmentioning
confidence: 86%
“…Accumulating evidence of the antitumor activity of essential oils (18,19) supports this material as one of these drug sources. In a previous paper (1), we showed that the EO of M. officinalis was cytotoxic to several cancer cell lines but its effect on GBM cells was not investigated.…”
Section: Discussionmentioning
confidence: 86%
“…Essential oil hydrodistilled at 100°C was found to have higher potency than the essential oil prepared at 78°C in cytotoxic effect. (Suhail et al, 2011).…”
Section: Breast Cancermentioning
confidence: 95%
“…A comparison of a large variety of essential oils performed by Lis-Balchin et al (1998) showed that frankincense oil was active against bacteria, fungi and also exerted anti-oxidative activity. Frank et al (2009) and Suhail et al (2011) performed various experiments with human breast and bladder tumor cell lines, which resulted in both cases in tumor-cell specific cytotoxicity of the essential oil. Although most of these studies characterized the composition of their essential oil samples by GC-MS measurements, the activity was never traced back to fractions or isolated compounds in the complex mixture.…”
Section: Considerations Regarding Potential Physiological Activity Ofmentioning
confidence: 97%